Ochrona dóbr materialnych w postępowaniu w przedmiocie wydania decyzji o środowiskowych uwarunkowaniach zgody na realizację przedsięwzięcia - Daniel, Paweł (Kwartalnik Prawa Publicznego, 2013)
Under the Council Directive 85/337/EEC of 27.6.1985 on the assessment of the effects of certain public and private projects on the environment and the Directive 2011/92/EU of the European Parliament and of the Council of 13.12.2011 on the assessment of the effects of certain public and private projects on the environment, the environmental impact assessment must identify, describe and assess in an appropriate manner, in the light of each individual case the direct and indirect effects of a project on the material assets. The same requirement can be find in the polish act on access to information on the environment and its protection, the community’s participation in protection of the environment and on environmental impact assessments. Therefore the aim of the article was to present as to which scope the material assets must be taken into account during the environmental impact assessment. The study shows that the administrative bodies are obliged to take into account the material assets during the environmental impact assessment. However this consideration does not include the assessment of the effects which the project under examination has on the value of material assets. The impact of the project on the material assets must be taken into consideration during its global evaluation and in particular can have a decisive influence on the variant of the project which is to be completed.